International Tourism as a Neoliberal Practice of Chinese Influence in the Western Balkans - Parfinenko, Anatoliy; Парфіненко, Анатолій Юрійович (Institute of International Relations, Taras Shevchenko National University of Kyiv, 2021)
The article reveals China's geostrategic interests in the Western Balkans. The paper highlights the main directions of Beijing's political and economic cooperation with the countries of the region, the impact of these processes on the foreign policy orientations of the Balkan countries. The focus is on assessing the international political potential of Chinese outbound tourism as a tool for neoliberal influence on the host destinations of the Western Balkans. The work consists of three interrelated parts. The first part, within the neoliberal paradigm, reveals the understanding of tourism as a factor of international political interaction and the establishment of "complex interdependence". For China, which generates the largest outbound tourist flow, these human communications provide the possibility of indirect influence on host destinations through the created economic dependence and the approval of "official tourist destinations." The second part of the study highlights the Chinese approach to the Western Balkans. It is motivated by the implementation of a large-scale project of the New Silk Road "Belt and Road Initiative", designed to create a cross-border transport and logistics network to accelerate the delivery of Chinese goods to European markets. In the context of this project, the countries of the Western Balkans have become a geographical "entry point" for both land and sea corridors of the new Silk Road, which connect the markets of Europe and Asia. The third part of the publication shows that China's international political and investment activity in the Western Balkans is based on a network of transnational social ties created under the auspices of the state. An appropriate place among them is given to tourist flows from China, whose communication strategies influence emotional and commercial involvement, as well as a positive perception of China in the region. It has been concluded that the intensification of tourist contacts and the related liberalization of mobility regimes serve as an important factor in strengthening the complex asymmetric interdependence of the Balkans with China. In the long term, this will strengthen Beijing's position in Europe, especially in the context of global competition with the United States.
Стаття розкриває геостратегічні інтереси Китаю в регіоні Західних Балкан. Висвітлено основні напрямки політико-економічної взаємодії Пекіну з країнами регіону, вплив цих процесів на зовнішньополітичні орієнтири балканських країн. В центрі уваги – оцінка міжнародно-політичного потенціалу китайського виїзного туризму як інструменту неоліберального впливу на приймаючі дестинації Західних Балкан. Робота складається із трьох взаємопов’язаних частин. У першій частині у межах неоліберальної парадигми розкрито розуміння туризму як чинника міжнародно-політичної взаємодії та встановлення «комплексної взаємозалежності». Для Китаю, який генерує найбільший за обсягом виїзний туристичний потік, ці людські комунікації відкривають можливість опосередкованого впливу на приймаючі дестинації через створювану економічну залежність та затвердження «офіційних туристичних напрямків». У другій частині дослідження висвітлено китайський підхід до Західних Балкан. Він зумовлений реалізацією масштабного проекту Нового шовкового шляху «Один пояс, один шлях», покликанного створити транскордонну транспортно-логістичну мережу для прискорення доставки китайських товарів на ринки Європи. В контексті даного проекту країни Західних Балкан перетворилися на географічну «точку» входу як для суходільного, так і для морського коридорів нового Шовкового шляху, які сполучають ринки Європи та Азії. У третій частині публікації показано, що міжнародно-політична та інвестиційна активність Китаю на Західних Балканах спирається на створювану під егідою держави мережу транснаціональних соціальних зв’язків. Належне місце серед них відводиться туристичним потокам з Китаю, комунікативні стратегії яких впливають на емоційну та комерційну залученість, а також позитивне сприйняття Китаю в регіоні. Робиться висновок, що інтенсифікація туристичних контактів та пов’язана із цим лібералізація режимів мобільності виступають важливим чинником посилення комплексної асиметричної взаємозалежності Балкан від Китаю. В довгостроковій перспективі це посилюватиме позиції Пекіну в Європі, особливо в контексті глобальної конкуренції зі США.
Keywords: Western Balkans; China; Foreign policy; Belt and Road Initiative; International tourism; Tourist flows